Analysis of Handling State Losses In Corruption Crimes - Mulyono Mulyono; Eny Maryana (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Handling of corruption offenses. Article 4 of Law No. 31 of 1999 states that "The return of state or national financial losses does not eliminate the criminal prosecution of the perpetrators of criminal acts as referred to in Articles 2 and 3. The existence of state losses in a case and the amount of the loss are very important, and currently there is still controversy, both regarding the evidence presented and the interpretation of "state losses" in corruption cases. To determine the amount of state losses in corruption cases, if the case is simple, the determination is made by the Prosecutor's Office. If the case requires a thorough audit, the Audit Board of Indonesia (BPK) or the Financial Supervisory Agency under Article 22 and Article 23 of Law No. 15 of 2004 concerning Examination of State Financial Management and Responsibility jo Article 1 number (16) of Law No. 15 of 2006 concerning the Audit Board of Indonesia regulates the mechanism for compensation in the event of a shortfall or loss of state funds. Law No. 15 of 2016 is contained in BPK Regulation No. 3 of 2007 concerning Procedures for Resolving Compensation for Treasurers jo the Audit Board of Indonesia Regulation No. 2 of 2010 concerning Monitoring of the Implementation of Follow-up Actions on the Results of the Audit Board of Indonesia's Audit under Article 3 paragraph (3). According to the explanation in Law No. 31 of 1999 concerning Eradication of Corruption, state finance refers to all state wealth in any form, whether separated or not, including all parts of state wealth and all rights and obligations arising from it. According to Law No. 31 of 1999, state financial loss is the reduction of state wealth caused by an illegal act, abuse of authority/opportunity or means available to a person due to their position or status, a person's negligence, and/or circumstances beyond human capability (force majeure). State losses are defined as a definite and certain shortage of money, valuable papers, and goods as a result of unlawful acts, whether intentional or negligent.